FWM-Minimizing Channel Allocation Algorithmic Scheme for Multichannel DWDM Transmission System - Ashira Jumpates; Yuttapong Rangsanseri; Suthichai Noppanakeepong; Nainapas Injoungjirakit (My University, 2017)
In this paper, we propose a novel channel allocation scheme, i.e., the asymmetrically paired repeated unequally spaced (APRUS) scheme, for the dense wavelength division multiplexing (DWDM) transmission system. The APRUS scheme is capable of virtually eliminating the four-wave mixing (FWM) noise in the DWDM system, thus effectively addressing the FWM problem plaguing the conventional equally spaced (ES) channel allocation scheme. The APRUS allocation scheme was simulated and validated on four performance metrics; the number of FWM frequencies, total FWM power, total FWM efficiency and bit error rate. The simulation results revealed that the APRUS scheme outperforms the conventional ES regime on all four metrics. In addition, the FWM noise under the APRUS scheme is negligible such that no optical filters are required to filter out the noise at the DWDM's receiving end. Moreover, an extra signal channel is accommodated under the APRUS allocation scheme, which is equivalent to a gain of 10Gbit/s data transfer rate.
Keywords: Spectral Efficiency; Channel allocation schemes; Four-wave mixing; Optical Network Technologies